2022
DOI: 10.1021/acsami.2c00532
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Methylene Blue-Embedded Intragastric Satiety-Inducing Device to Treat Obesity

Abstract: Bariatric surgery is the most effective treatment for weight recidivism, and endoscopic bariatric treatment has been developed for a similar effect without anatomical modification. An intragastric satiety-inducing device (ISD) is a minimally invasive approach to induce satiety by continuously pressing the stomach and stimulating ghrelin-producing cells. To enhance the therapeutic effects of ISD, photodynamic therapy (PDT) can be combined by generating singlet oxygen under laser irradiation. Methylene blue (MB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Tissue damage induced by PDT occurs when the PS generates ROS after laser irradiation at a specific wavelength, which can in turn induce cellular apoptosis via oxidative stress. ,, TUNEL-stained tissues of the PDT-treated rat esophagus indicated that controlled ROS release led to localized tissue damage and induced apoptosis. A single session of localized PDT using PS-embedded silicone covered devices demonstrated therapeutic effects for obesity, but the effects lasted for only 2 weeks. Damaged tissues gradually regenerated at 3–4 weeks after PDT. , Despite only a week of follow-up results in our study, therapeutic effects with apoptotic tissue changes were well maintained. The stent was placed after localized PDT to maintain the patency of the PDT-treated esophagus and prevent the possibility of esophageal stricture formation after the PDT procedure.…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…Tissue damage induced by PDT occurs when the PS generates ROS after laser irradiation at a specific wavelength, which can in turn induce cellular apoptosis via oxidative stress. ,, TUNEL-stained tissues of the PDT-treated rat esophagus indicated that controlled ROS release led to localized tissue damage and induced apoptosis. A single session of localized PDT using PS-embedded silicone covered devices demonstrated therapeutic effects for obesity, but the effects lasted for only 2 weeks. Damaged tissues gradually regenerated at 3–4 weeks after PDT. , Despite only a week of follow-up results in our study, therapeutic effects with apoptotic tissue changes were well maintained. The stent was placed after localized PDT to maintain the patency of the PDT-treated esophagus and prevent the possibility of esophageal stricture formation after the PDT procedure.…”
Section: Resultsmentioning
confidence: 49%
“…In this study, a Ce6-embedded silicone-covered SEMS was successfully fabricated based on the well-established Ce6-embedded silicone membrane to perform localized and endoluminal PDT. The Ce6-embedded silicone-covered SEMS demonstrated its significance in terms of improved PS bioavailability and better practicality for laser irradiation . This study demonstrated that the Ce6-embedded silicone-covered SEMS validates the optimized irradiation energy doses and PDT-induced tissue changes in an in vivo rat esophagus.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In recent years, photodynamic therapy (PDT) has become a focal point of scientists by reason of the predominant advantages to overcome the resistance and side effects of multidrugs in conventional therapies. Normally, PDT comprises three important essential factors in the treatment: an excitation light source, oxygen in tissues, and a photosensitizer (PS). In the presence of light excitation, the PS is capable of transferring the absorbed photon energy into an electron, which induces oxygen to generate reactive oxygen species (ROS) and ultimately triggers oxidative photodamage to kill tumor cells and damage tissue. , …”
Section: Introductionmentioning
confidence: 99%
“…In the presence of light excitation, the PS is capable of transferring the absorbed photon energy into an electron, which induces oxygen to generate reactive oxygen species (ROS) 5 and ultimately triggers oxidative photodamage to kill tumor cells and damage tissue. 6,7 Because PS is a core issue in PDT, tremendous effort has been made to find a fresh PS that possesses the virtue of high stability, high light conversion efficacy, and sensitivity to irradiation. 8 Lately, metal-free graphitic carbon nitride (g-C 3 N 4 ) with a band gap energy of approximately 2.71 eV has been considered as a promising PS.…”
Section: ■ Introductionmentioning
confidence: 99%